Підвищення енергетичної ефективності тягового колекторного електроприводу для маневрових тепловозів - Шайда, Віктор Петрович; Юр'єва, Олена Юріївна; Лисенко, Євген Вячеславович; Сич, Олег Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Досліджено показники енергетичної ефективності тягового електроприводу у режимах роботи з частиною працюючих тягових електродвигунів. Показано, що оптимізація кількості працюючих двигунів залежно від режиму руху дозволяє підвищити ККД тягового електроприводу. Доцільною є динамічна зміна кількості працюючих електродвигунів, що забезпечить стабільність тягового зусилля при рушанні та підвищення енергоефективності тягового приводу при русі. Результати досліджень можуть бути використані при модернізації. This paper investigates the improvement of energy efficiency in the traction collector electric drive of shunting diesel locomotives, specifically the ChME3 locomotives. The study focuses on the operation of traction drives with a partial number of working traction motors under various control positions of the driver's controller. Using mathematical modelling and simulation, the authors analysed the efficiency of the traction drive system under different configurations and speeds. The results demonstrate that operating with fewer traction motors at lower power settings (positions 1 to 4) can significantly increase the overall efficiency of the drive system, especially at certain speed ranges. For instance, using two motors at low speeds yields higher efficiency compared to using all six motors. The study also highlights the importance of dynamically adjusting the number of active motors depending on the locomotive’s operational mode—more motors are recommended during startup to ensure traction stability, while fewer motors can be used during steady movement to reduce energy consumption. The findings suggest that such an approach can lead to reduced fuel consumption, lower maintenance costs, and improved performance of modernized locomotives. The proposed methodology and results are applicable to the modernization of other diesel locomotives equipped with collector-type traction motors. This research contributes to the broader goal of enhancing the sustainability and cost-effectiveness of railway transport systems through intelligent energy management strategies.
Increasing the energy efficiency of the traction collector electric drive for shunting diesel locomotives
Keywords: рухомий склад; локомотив; тяговий електропривод; тяговий електродвигун; енергоефективність; rolling stock; locomotive; traction electric drive; traction electric motor; energy efficiencyrolling